(untitled) (Research, Society and Development, 2020)
This work brings with it an analytical profile of the population that lives in the urban preservation area (APP) of Igarapé Ilha do Coco in the municipality of Parauapebas with the purpose of socioenvironmentally analyzing the profile of these residents, creating parameters that measure the influences resulting from the occupation of this space. The mapping was carried out to assess the particularities of the area located in the neighborhood mentioned above, and also the application of a socio-environmental questionnaire where the residents were able, through their answers, to provide us with information about the real impacts of the occupation of the APP. The survey was carried out in a section of the streets above, and the other after the stream bed, thus making around 30 residences. During the work, sustainability profiles were pointed out, in which criteria were raised, such as family income, general waste disposal, education level, interest in social and environmental actions in the community, actions that inhibit or not the pollution of the water body, among others, making it possible the creation of socio-environmental data on residents, where low levels of education were found, family income below a minimum wage, many families have basic income from government programs and also services for the collection and final disposal of scarce residues, thus, many residents burn this waste in the open air and in addition there is contamination of the water body by the release of waste. Bringing up the need to incorporate these residents into public policies that make them co-participants and also protagonists of these actions in the midst of their community.